PERAN ORANG TUA DALAM MENANAMKAN MINAT ANAK MENYIMAK CERAMAH DHAMMA (DHAMMADESANA) DI KABUPATEN WONOGIRI JAWA TENGAH - Santi Paramita (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
The purpose of this research is to find out how the role of parents in instilling children'sinterest in listening to Dhamma sermon in Wonogiri Regency, also knowing the reason of a childis interested in listening to sermon of Dhamma. This study used qualitative research methods.The approach used is case studies. The role of parents in instilling children's interest in listeningto Dhamma sermon (dhammadesana), is carried out through the role of educating, guiding,habituating, giving and setting an example, in addition to involving children in pujabhaktiactivities. The thing that causes children to be interested in listening to Dhamma lectures is thecuriosity of the theme or the subject, the presence of lecturers, who are prominent or famous, inaddition to the attraction of the location or place of the Dhamma sermon. Another externalfactor that is not from the internal factor nor the parents either is from the teacher of Buddhisteducation who provides motivation.Keywords: Parents, children's interests, sermon of dhamma